SIMULATION OF THE FLOATING PHOTOVOLTAIC SYSTEM IN THE NAPIQUE LAGOON TO EVALUATE THE SUPPLY OF ELECTRICITY DEMAND IN THE DISTRICT OF CASTILLA, PIURA - JIMENEZ, SANTIAGO LINDER RUBINOS (2024)
CURRENTLY, THERE HAS BEEN A SIGNIFICANT INCREASE IN THE INSTALLATION OF PHOTOVOLTAIC (PV) MODULES ON WATER SURFACES, DUE TO THE NATURAL CAPACITY OF WATER TO COOL AND KEEP THE MODULES FRESH, GENERATING A REDUCTION IN THE LOSS OF THERMAL ENERGY AND AVOIDING THE LOSS OF EFFICIENCY DUE TO OVERHEATING. HOWEVER, IN PERU THE APPLICATION OF PHOTOVOLTAIC SYSTEMS ON FLOATING SURFACES IS NULL AND THE STUDIES PUBLISHED REGARDING THEIR APPLICATIONS ARE LIMITED SO FAR. THE OBJECTIVE OF THIS RESEARCH IS TO CARRY OUT A REALISTIC SIMULATION OF A FLOATING PHOTOVOLTAIC SYSTEM DRIVEN BY CLIMATE AND BASED ON ENERGY DEMAND IN THE DISTRICT OF CASTILLA. PVSYSTEM AND GLOBAL SOLAR ATLAS WERE USED AS CALCULATION AND SIMULATION TOOLS IN THIS STUDY. THE RESULTS SHOW THAT 1GWH IS NECESSARY TO COVER THE ELECTRICITY DEMAND AND THAT WITH THE FPV AROUND 76.28 MWH IS PRODUCED, LESS THAN WHAT IS NECESSARY PER YEAR WITH AN AVERAGE PR OF 83.88%. THE ÑAPIQUE LAGOON IS AN IDEAL LOCATION FOR THE IMPLEMENTATION AND INSTALLATION OF THE FPV SYSTEM BECAUSE IT COVERS 92.37% OF THE ENERGY DEMAND OF THE DISTRICT OF CASTILLA, WHICH CAN BE COMPLEMENTED WITH LOW REQUIREMENTS FOR A DIESEL GENERATOR. © 2024 IEEE.